Proses Pengambilan Keputusan Nasabah Bank Syariah Dalam Memilih Produk Pembiayaan Kepemilikian Rumah (Studi Kasus Nasabah Bank Muammalat KCI Darmo Surabaya) - Putra, Bima Kurnia; Hasib, Fatin Fadhilah (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The purpose of this research is to find out the decision making process of the customer of Muamalat Bank in choosing mortgage product. The process comprises problem recognition, information search, evaluation of alternatives, product choice, and the outcomes.A qualitative approach is applied in this research with the descriptive case study method. The collection of data uses purposive sampling to determine the key informant and uses snowballing sampling to determine the informants. The key informant in this research is an employee of Muamalat Bank. Meanwhile the infomants consist of four customers of Muamalat Bank. Two of them take murabahah contract and the rest takes musyarakah mutanaqisah contract. The collection of data is conducted through several steps including comprehensive exploration, focus exploration, and confirmation step. The data analysis in this research uses domain, taxonomic and componential analysis.The result of this research shows that both the murabahah and musyarakah mutanaqisah customers had already passed through five steps in decision making process comprises problem recognition, information search, evaluation of alternatives, product choice, and outcomes. The difference between two of them is revealed in the problem recognition and the product choice. The customer choose the mortgage contract based on some features.